70.1k views
5 votes
Please help me with this.

Please help me with this.-example-1
User MohanRajNK
by
5.0k points

2 Answers

3 votes

Answer:

1. x - 2y = -6

2. x + 3y = 0

Explanation:

The Standard form of an eqaution of a line:


Ax+By=C

1.


y=(1)/(2)x+3 multiply both sides by 2


2y=2\!\!\!\!\diagup^1\cdot(1)/(2\!\!\!\!\diagup_1)x+(2)(3)


2y=x+6 subtract x from both sides


-x+2y=x-x+6


-x+2y=6 change the signs


x-2y=-6

2.


y-2=-(1)/(3)(x+6) multiply both sides by 3


3y-(3)(2)=3\!\!\!\!\diagup^1\cdot\left(-(1)/(3\!\!\!\!\diagup_1)\right)(x+6)


3y-6=-(x+6)


3y-6=-x-6 add 6 to both sides


3y-6+6=-x-6+6


3y=-x add x to both sides


x+3y=-x+x


x+3y=0

User Alexsander Akers
by
5.7k points
4 votes

Answer:

-x+2y=6 and x+3y=0

Explanation:

Ax+By=C

y=1/2 x+ 3

y= x+6/2

2y=x+6

-x+2y=6------------1

y-2=-1/3(x+6)

3(y-2)= -(x+6)

3y-6=-x-6

3y+x=-6+6

x+3y=0------------2

User Elliot Gorokhovsky
by
5.4k points